Analisis Sistem Kendali Terbang dengan Gain Scheduling Pada Pesawat Efek Permukaan - Sayuti Syamsuar (Research and Development Agency of The Ministry of Transportation, 2017)
This paper provides an overview of the design of adaptive flight control system of wing in surface effect craft Lippisch configuration 8 passengers capacity during cruise in the low speed and low altitude. The control system will be used the control surface, such as elevator deflection as input and pitch angle deflection as output response or by using engine throttle setting as input and others output response in the longitudinal mode. This paper describes some methodologies control system method and analysis such as PID controller system with gain scheduling approach, and root locus method. The observable matrices (4 x 4) on the longitudinal mode that used in the control system became from aerodynamic derivative parameters of 8 seaters configuration that calculated by DATCOM numerical simulation or wind tunnel test result and dummy data. Kajian ini merupakan rancangan sistem kendali terbang adaptif pada pesawat efek permukaan konfigurasi Lippisch kapasitas 8 orang saat terbang mendatar pada kecepatan dan ketinggian terbang rendah. Sistem kendali terbang yang digunakan, seperti defleksi elevator sebagai input dan defleksi sudut pitch sebagai respon output atau penggunaan defleksi throttle mesin sebagai input dan parameter respon output lain pada gerak matra longitudinal. Kajian menjelaskan penggunaan beberapa metodologi dan analisis sistem kendali terbang adaptif, seperti kontroler PID dengan pendekatan gain scheduling, dan metoda root locus. Matriks ruang keadaan berukuran (4 x 4) pada matra longitudinal yang digunakan pada sistem kendali terbang adaptif diperoleh dari parameter turunan aerodinamika hasil perhitungan numerik DATCOM atau hasil uji terowongan angin dan data dummy.